Qualidade de vida relacionada à saúde e sua associação com excesso de peso de escolares - Oliveira, Milena Carolina Silva Castro (2016)
The importance of investigating quality of life (QoL) in certain groups has been growing as an evaluation measure of treatment results in the health area. According to the WHO, QoL is the individual’s perception of his position in life, in the context of the culture and value system in which he lives and in relation to his objectives, expectations, standards and concerns. The aim of this study was to investigate quality of life in middle and high school children and adolescents and its association with obesity and sedentary activities at Escola Pública Estadual Aristides Rodrigues Simões, in the city of Herculândia – SP, through the application of a sociodemographic questionnaire and the Brazilian version of the generic questionnaire Pediatric Quality of Life InventoryTM (PedsQLTM 4.0). The evaluation of the students’ physical activity level was carried out by means of the Physical Activity Questionnaire (IPAQ) - Short Form. For the evaluation of the nutritional state anthropometric measures of weight, height and waist circumference were taken, in order to calculate the Body Mass Index (BMI) and Waist-to-Height Ratio (WHtR). The students were grouped under the categories “Not Overweight” and “Overweight” and compared, by gender, in relation to the domains of HRQOL, by means of Student t Test at 5% significance level (p < 0.05). The results gathered allowed to infer that, in general, there is no difference in QoL for students in both groups, either by gender or school level, as well as the mean scores for the domains were higher than 54,6, showing that the QoL of the investigated children and adolescents is considered good